Description of the Level of Happiness of Nursing Students who are Writing Their Mini-Thesis - Andini, Wilda; Komariah, Maria; Hidayati, Nur Oktavia (Indonesian Journal of Global Health Research, 2024)
The process of preparing a mini thesis in students is often accompanied by high levels of stress because they face strict academic demands. One factor that can help students overcome stress is to increase happiness. Final semester students need happiness to feel comfortable during the process of preparing a mini-thesis. Unhappy students can have a negative impact on their academic performance, motivation, and overall well-being. Objective: This study aims to determine the description of the level of happiness of college students who are preparing a mini-thesis at the Faculty of Nursing, Padjadjaran University. Method: The research design used is descriptive quantitative. The population in this study were college students who were preparing a mini-thesis at the Faculty of Nursing, Padjadjaran University as many as 176 college students, but the respondents were 130. Data was collected using Oxford Happiness Questionnaire (OHQ) designed by Hills & Argyle with validity test results ranging from 0.26-0.69 and the reliability test results 0.91. Univariate analysis was carried out using descriptive statistics. Results: The results showed that in general (72,3%) college students of the Faculty of Nursing, Padjadjaran University who were preparing a mini-thesis were in the category of tending to be happy and a small proportion (27,7%) were in the category of tending to be unhappy. Conclusions: The conclusion of this study is that most college students have a high sense of comfort, pleasure, joy, and peace to complete the mini-thesis.